Demokrasi Indonesia di tengah arus digitalisasi: Demokrasi Indonesia di tengah arus digitalisasi - Qomariah, Siti Wasilatul (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has significantly transformed democratic practices and patterns of political participation in Indonesia, particularly among young people. Social media and the internet have become new public spaces that enable citizens to access political information, voice their aspirations, and engage in democratic activities more quickly and openly. This study aims to analyze the development of Indonesian democracy in the midst of the digital era, the forms of political participation among young people, and the various challenges that have emerged in digital democracy. This study employs a literature review method, utilizing journals, academic articles, and relevant references on digital democracy and youth political participation. The findings indicate that digitalization has enhanced youth political participation through digital campaigns, online discussions, and internet-based social movements. However, digital democracy also presents several challenges, including hoaxes, political disinformation, social polarization, identity politics, low digital literacy, and the phenomenon of slacktivism. Therefore, strengthening political education, improving digital literacy, and developing innovations in digital democracy are crucial for creating a more participatory, inclusive, transparent, and high-quality democracy in Indonesia in the digital age.